Adenocarcinoma of the small bowel: A surgical dilemma - Vagholkar Ketan; Mathew Tony (The Saudi Journal of Gastroenterology, 2009)
Malignant tumors of the small intestine are among the rarest types of gastrointestinal cancers. Due to their infrequent occurrence and the multitude of tumor types (viz, adenocarcinomas, carcinoids, sarcomas, and lymphomas), not much is known about their natural history and presentation, and there is often delay in the diagnosis. Adenocarcinoma is the commonest histologic type of small bowel cancer. There are no prospective randomized trials that have elucidated the best diagnostic and therapeutic options for this rare condition. In this article, a case of adenocarcinoma of the jejunum presenting as an abdominal lump is presented, along with a review of the literature.